The adoption of technology in Islamic information literacy among young moslem - Puspita, Rosana Eri; Badi’ati, Alfi Qonita (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
The young generation is a digital native, which information easier to get with an Information system. So, it is important to measure information literacy among young Muslims about Islamic information. This study investigates the factors that influence the use of technology in searching for literature relating to Islam among the younger generation. The approach taken in this research is quantitative. Data is collected with the help of research instruments in the form of online questionnaires. The population in this study is the younger generation, who tend to be digital natives. The sample size in this study was 100. The testing tool in this study used SPSS, and a regression method was conducted to determine the effect of this research variable. The result shows that perceived usefulness has a significant impact on behavioral intention in Islamic information literacy. Besides, perceived ease of use also positively and significantly affects Islamic information literacy's behavioral intention. The study suggests there need to be some actions so that the younger generation can be smarter in using technology in Islamic information literacy. This study was more focused on examining acceptance for the young Moslem generation in developing countries. This study has an important role in developing TAM's scientific repertoire theory from information technology in Islamic information literacy.